2016
DOI: 10.1136/postgradmedj-2015-133865
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of pathology tests and imaging study in the diagnosis of acute appendicitis

Abstract: Young female patients have highest risk of being falsely diagnosed with acute appendicitis and hence unnecessary surgery. Bilirubin and lipase exhibit no correlations with acute appendicitis. Combined interpretation of WCC or CRP abnormal results yields competitive sensitivity as CT. Hencewe would suggest that, under the appropriate clinical context, one can use both WCC and CRP as a simple tool to support the diagnosis of appendicitis. If both tests show normal results, we would highly recommend considering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
15
1
6
Order By: Relevance
“…In our study, the majority of the cases were younger compared to elderly. Although there were more studies in the literature that showed more women are diagnosed with AA, there were more males in the population with an AA diagnosis in our study (14).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In our study, the majority of the cases were younger compared to elderly. Although there were more studies in the literature that showed more women are diagnosed with AA, there were more males in the population with an AA diagnosis in our study (14).…”
Section: Discussionmentioning
confidence: 55%
“…The incidence of AA at an early age is higher than that in the elderly population (13,14). However, the presentation of these diseases in younger patients may be different from that in middle-aged and older patient groups.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The lack of histological outcomes from the surgically removed specimens in our cohort does 226 limit our ability to establish definitively whether misdiagnosis occurred, however the frequency 227 of normal pathological specimens following surgical removal has previously been described, 228 with 25.7% (64/249) of patients in a recent study having a normal appendix following 229 appendectomy for suspected appendicitis. 46 Our assessment of final diagnoses in inpatients after This study compares favourably to a previous study demonstrating increased surgical risk in 260 undiagnosed CD patients (n=476). 48 Our current study is significantly larger than that previous 261 work, helping to establish high statistical precision and calculation of important subanalyses, 262 including stratified analyses according to sex, age and calendar period of CD diagnosis.…”
mentioning
confidence: 69%